LTE multi-user downlink throughput performance modeling and analysis - Zhicheng WEN (Dianxin kexue)
Aiming at LTE multi-user downlink throughput, it was analyzed that from time domain and frequency domain of LTE resources, user location, UE category and downlink MIMO modes, also combined with the characteristics, influencing factors, action processes of time-domain and frequency-domain scheduling algorithms under multi-user conditions. The multi-user downlink throughput analysis and estimation model was then built based on this, and the model was used to analyze a real example. It would be beneficial for LTE performance optimization.